Analisis Kemampuan Representasi Matematis Siswa dalam Menyelesaikan Soal Matematika Ditinjau dari Tipe Kepribadian Florence Littauer - Aini, Khafidhoh Nurul; Hidayah, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research purpose to describe students' mathematical representation abilities in solving mathematics problems in terms of Florence Littauer's personality type. This type of research is descriptive qualitative with the research subjects being class VIII students at SMPN 2 Sukodadi, totaling 8 students. This research uses technical triangulation, a Florence Littauer questionnaire to determine students' personality types and tests used to determine students' mathematical representation abilities. The results of this research show that students with a sanguine personality with high ability can complete visual and symbolic representations, students with moderate ability are less able to complete verbal representations, and students with moderate ability are less able to complete all indicators of mathematical representation ability. Choleric personality students with medium ability are less able to complete visual and symbolic representation indicators, low ability students are not able to complete verbal representations, and students with low ability are not able to complete all indicators of mathematical representation ability. Melancholic personality students with high abilities can complete all mathematical representation abilities. Phlegmatic personality students with low abilities have not been able to complete all mathematical representation skills